The early years of school : Teaching and learning - Briggs, Freda; Potter, Gillian (South Melbourne, Vic. : Addison Wesley Longman, 1999)
Early childhood education: the profession in focus. The foundations of early childhood education. An introduction to the early years of school. Transition in early childhood education. Understanding children in the early years of school. Assessment and observation in education...
Keywords: Education; Primary school teaching; Education, Primary; Primary school teaching; Education, Primary -- Aims and objectives